1997
DOI: 10.1161/01.cir.96.8.2617
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Atrioventricular Junction Ablation and DDDR Mode-Switching Pacemaker Versus Pharmacological Treatment in Patients With Severely Symptomatic Paroxysmal Atrial Fibrillation

Abstract: In patients with paroxysmal AF not controlled by pharmacological therapy, Abl+Pm treatment is highly effective and superior to drug therapy in controlling symptoms and improving quality of life. The discontinuation of drug therapy exposes patients to further recurrences of paroxysmal AF and the risk of developing permanent AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(134 citation statements)
references
References 32 publications
5
123
0
6
Order By: Relevance
“…Previous studies in HFpEF patients who underwent AVN ablation and permanent RV pacing for refractory AF showed inconsistent results with respect to improvement in LV function 1, 2, 28, 29. Permanent RV pacing may not be an ideal option for patients with diastolic heart failure with preserved ejection fraction 4, 30.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies in HFpEF patients who underwent AVN ablation and permanent RV pacing for refractory AF showed inconsistent results with respect to improvement in LV function 1, 2, 28, 29. Permanent RV pacing may not be an ideal option for patients with diastolic heart failure with preserved ejection fraction 4, 30.…”
Section: Discussionmentioning
confidence: 98%
“…Multiple clinical studies have demonstrated improved quality of life following atrioventricular node (AVN) ablation and permanent right ventricular (RV) pacing in patients with symptomatic atrial fibrillation (AF) refractory to optimal medical therapy 1, 2, 3, 4. However, several studies performed over the last decade have demonstrated that conventional long‐term RV apical pacing can increase the risk of death and heart failure hospitalization 4, 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…6 Our results relating stroke to hypertension, systolic blood pressure, and diabetes in AF patients are also similar to published studies in developed countries. 7,8 However, the findings of severity of hypertension relating to risk of stroke appear to be particularly interesting. Although the systolic blood pressure taken on admission was casual, we think that the control of blood pressure was poor for those patients with high systolic blood pressure.…”
Section: Risk Factors For Stroke In Nonrheumatic Af Patientsmentioning
confidence: 99%
“…Indeed, in contrast to other ablative procedures in which the ablation erases the electrophysiologic substrate of the disease, ablate and pace only works indirectly, changing an irregular and fast ventricular rate into a regular, pacemaker-dependent, normofrequent rate. It could also be said that ablate and pace replaces one disease (uncontrolled AF) with another (iatrogenic complete AV block) [49]. Moreover, the procedure is completed by a pacemaker implant, with all the short-and long-term complications associated with a device implant procedure.…”
Section: Rationale and Indications For Ablate And Pacementioning
confidence: 99%